Targeting Thyrointegrin αvβ3 Using Fluorobenzyl Polyethylene Glycol Conjugated Tetraiodothyroacetic Acid (NP751) in Acute Myeloid Leukemia - Darwish, Noureldien H. E.; Glinsky, Gennadi V.; Sudha, Thangirala; Mousa, Shaker A. (Frontiers in Oncology, 2022)
Background Acute myeloid leukemia (AML) is associated with poor long-term survival, even with newer therapeutic agents. Here, we show the results of our preclinical study, in which we evaluated the efficacy of a new thyrointegrin αvβ3 antagonist, named fluorobenzyl polyethylene glycol conjugated tetraiodothyroacetic acid (fb-PMT). Methods and Results fb-PMT (NP751) is a potent αvβ3 antagonist of molecular weight of 2,478.9 Da. it represents a conjugate of tetraiodothyroacetic acid (tetrac) and monodisperse polyethylene glycol (PEG36), with a 4-fluorobenzyl group capping the other end of the PEG. fb-PMT effectively suppresses the malignant growth of human acute myeloid leukemia (AML) after successful engraftment in transgenic NSG-S xenograft mouse models of either established human AML cell line or primary AML cells. Daily treatment with fb-PMT (1–10 mg/kg body weight) subcutaneously (s.c.) for 3–4 weeks was associated with marked regression of leukemogenesis and extended survival in both models. The efficiency of the fb-PMT therapy was verified using in vivo imaging system (IVIS) imaging, flow cytometry, and histopathological examination to monitor the engraftment of leukemic cells in the bone marrow and other organs. fb-PMT therapy for 3–4 weeks at 3 and 10 mg/kg daily doses exhibited significant reduction (p < 0.0001) of leukemic cell burden of 74% and >95%, respectively. All fb-PMT-treated mice in the 10 mg/kg treatment arm successfully maintained remission after discontinuing the daily treatment. Comprehensive fb-PMT safety assessments demonstrated excellent safety and tolerability at multiple folds above the anticipated human therapeutic doses. Lastly, our genome-wide microarray screens demonstrated that fb-PMT works through the molecular interference mechanism with multiple signaling pathways contributing to growth and survival of leukemic cells. Conclusion Our preclinical findings of the potent anticancer activities of fb-PMT and its favorable safety profiles warrant its clinical investigation for the effective and safe management of AML.